2015
DOI: 10.1103/physrevlett.114.081103
|View full text |Cite
|
Sign up to set email alerts
|

Effective Potentials and Morphological Transitions for Binary Black Hole Spin Precession

Abstract: We derive an effective potential for binary black hole (BBH) spin precession at second post-Newtonian order. This effective potential allows us to solve the orbit-averaged spin-precession equations analytically for arbitrary mass ratios and spins. These solutions are quasiperiodic functions of time: after a fixed period, the BBH spins return to their initial relative orientations and jointly precess about the total angular momentum by a fixed angle. Using these solutions, we classify BBH spin precession into t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
256
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 131 publications
(257 citation statements)
references
References 41 publications
1
256
0
Order By: Relevance
“…Our new solutions for spin precession allow us to fully exploit the timescale hierarchy of Eq. (1), expanding and detailing the ideas put forward in our previous paper [28]. We showed that spin precession is quasiperiodic implying that the relative orientations of the three angular momenta are fully specified by a single parameter, the magnitude of the total spin, that oscillates on the precession time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our new solutions for spin precession allow us to fully exploit the timescale hierarchy of Eq. (1), expanding and detailing the ideas put forward in our previous paper [28]. We showed that spin precession is quasiperiodic implying that the relative orientations of the three angular momenta are fully specified by a single parameter, the magnitude of the total spin, that oscillates on the precession time.…”
Section: Introductionmentioning
confidence: 99%
“…2. The simple dependence of ξðS; φ 0 Þ on φ 0 motivates us to define two "effective potentials" [28] corresponding to the extreme cases cos φ 0 ¼ ∓1 for which L, S 1 and S 2 are all coplanar:…”
Section: B Effective Potentials and Resonancesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the range 10 < r/rg < 10 4 , the binary dynamics can be described using the spinning Taylor-expanded PN Hamiltonian. As in previous studies (Schnittman 2004;Kesden et al 2010a;Berti et al 2012;Gerosa et al 2013Gerosa et al , 2014Kesden et al 2015;Gerosa et al 2015a,b), we focus our analysis in this range. In the barycenter frame, the Hamiltonian depends on the canonical variables (r, p) and on the spins vectors.…”
Section: Secular Dynamicsmentioning
confidence: 99%
“…One of the most difficult aspects of studying the spinning black hole binary system is the problem of visualizing and analyzing the orientation of the two spins and the angular momentum in an informative way. Previous studies always describe the libration around the coplanar configurations as spin-orbit resonances (Schnittman 2004;Kesden et al 2010a;Berti et al 2012;Gerosa et al 2013Gerosa et al , 2014Kesden et al 2015;Gerosa et al 2015a,b). However, this description is not consistent with the expectation that the two normal modes of this problem become resonant, since for black hole binaries one frequency is usually smaller than the other (Racine 2008).…”
Section: Introductionmentioning
confidence: 99%